PELATIHAN PEMBUATAN RAISED BED DAN MEDIA TANAM TANAH SUBUR DI DESA BAUNG KECAMATAN SERUYAN HILIR - Suroto Suroto; Zul Erianto Suarja (Jurnal Pengabdian Kepada Masyarakat Agri Hatantiring, 2024)
Raised bed is a planting method in which the planting area is raised from the surrounding ground level using a frame or container made of wood, stone, metal, or other materials. The main purpose of raised beds is to improve soil drainage, reduce the risk of soil erosion, control weeds, and provide a better growing environment for plants. Baung is one of the villages in Seruyan Hilir sub-district, Seruyan, Central Kalimantan. Baung Village has plain topography with an altitude of <500 meters above sea level with the plain area consisting of lowlands, hilly plains and riverbanks. Baung Village is the right target area for training in making raised beds and fertile soil planting media because the environment, especially its yards, is subject to natural constraints for planting considering the frequent ebb and flow of river water which inundates the people's yards. In utilizing their yard land, the people of Baung Village to become a source of food security for their families are less well managed due to natural constraints, because the community is more focused on working to earn their main income so that the yard land they own does not produce products that can be utilized for consumption needs, so training activities for making raised bed planting media. Then by adding a method for making solid organic fertilizer which is done directly in the raised bed that has been prepared. The PKK women who took part in this activity seemed enthusiastic and played a direct role in the making process, because the materials and tools were simple and easy to obtain, and most of the PKK women were already used to working in the garden, so they did not experience any significant obstacles in its implementation. Keywords: Baung Village, Raised Bed, Organic Fertilizer